Judge Blaine Pettitt Retirement Luncheon at Fresno Hilton Hotel Ballroom - Watkins, Howard::::::::: (1985)
Judge Robert Mardikian speaking at lectern, Judge Blaine Pettitt, Alice Pettitt, Judge Denver C. Peckinpah seated